'Voyage across Cultures and Climes': Whiteness, Exoticisation and Alienation in David Kerr's Tangled Tongues. Issue 3 (2nd July 2020) - Mthatiwa, Syned
ABSTRACT: A reading of the poetry by David Kerr, a British mobile professional in southern Africa, shows that he does not only cast a critical and ironic look at the various cultures and socio-political behaviours he encounters in his sojourns, but also at himself as a white man and at the actions of white people in Africa. This paper focuses on selected poems from Tangled Tongues that deal with Kerr's positionality and sense of identity and those that depict the role of whites in Africa. I argue that in these poems Kerr highlights his sense of alienation and, using irony and humour, critiques the attitude and behaviour of whites as they relate to African people, their languages and way of life. A reading of the poetry also shows that Kerr is aware of the impact of white power and privilege in Africa and uses an ironic, self-denigrating and critical approach in dealing with his background as a strategy to destabilise whiteness.